2023
DOI: 10.34133/plantphenomics.0012
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Photosynthetic Pigments in Neopyropia yezoensis Using Hyperspectral Imagery

Abstract: Phycobilisomes and chlorophyll-a ( Chla ) play important roles in the photosynthetic physiology of red macroalgae and serve as the primary light-harvesting antennae and reaction center for photosystem II. Neopyropia is an economically important red macroalga widely cultivated in East Asian countries. The contents and ratios of 3 main phycobiliproteins and Chla are visible traits to evaluate its commercial quality. The traditional analytica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…After comparing the absorbance peaks from our CCA samples with red algae pigment literature, our results indicated that phycobilin absorbance peaks corresponded to PE, while peaks in the nonpolar pigments were caused by Chl a . The pigment extraction absorbance spectra provided a valuable reference to evaluate its relationship with spectral reflectance and build tailored indices, or “proxies.” Further studies on coralline algae pigmentation using HSI could focus on PC (detected in low quantities in this study), APC, chlorophylls, and carotenoids (Burdett et al., 2014; Che et al., 2023; Voerman, Marsh, et al., 2022).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…After comparing the absorbance peaks from our CCA samples with red algae pigment literature, our results indicated that phycobilin absorbance peaks corresponded to PE, while peaks in the nonpolar pigments were caused by Chl a . The pigment extraction absorbance spectra provided a valuable reference to evaluate its relationship with spectral reflectance and build tailored indices, or “proxies.” Further studies on coralline algae pigmentation using HSI could focus on PC (detected in low quantities in this study), APC, chlorophylls, and carotenoids (Burdett et al., 2014; Che et al., 2023; Voerman, Marsh, et al., 2022).…”
Section: Discussionmentioning
confidence: 93%
“…To improve regression algorithms, future studies could make use of additional sampling efforts to increase sample size and test multivariate analysis based on chemometrics or machine learning methods that can handle collinearity between predictors (i.e., different wavelengths from a spectrum), enabling the use of the whole spectral reflectance signature to measure different biochemical traits (Burnett et al., 2021; Che et al., 2023). Integration with multiple sensors, such as pulse amplitude modulation fluorometry (Burdett et al., 2012; Schwarz et al., 2005; Summers et al., 2023), along with measurements of different CCA response categories like calcification and primary production (Cornwall et al., 2019; Page et al., 2022), could further refine noninvasive assessments of their photo‐physiology response to different irradiance regimes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This demonstrates that VNIR–HSI can be applied to the rapid and accurate prediction of the pigment concentration. Che et al [ 25 ] analyzed the phenotypes of photosynthetic pigments in Neopyropia yezoensis for phycoerythrin (PE), phycocyanin (PC), allophycocyanin (APC) and Chla using VNIR–HSI. Two machine learning techniques, partial least squares regression (PLSR) and support vector machine regression (SVR), were employed in the prediction model after several pre-processing approaches.…”
Section: Introductionmentioning
confidence: 99%